INTERPRETATION OF HATE IN CRIMINAL LAW OR QUANTUM CRIMINOLOGY - Baumanis, Jānis (Administrative and Criminal Justice, 2016)
In an article about criminology is disclosed not very widespread method related to the hate essence and harmfulness, when it comes to the hate interpretation in criminal justice. Considering that to describe the feelings, emotions and passions is quite complex, the author is using fiction and theological reference for the existing knowledge, to show a hatred as manifestations of emotions existence and harmfulness. As a result, the author comes to the conclusions: 1. Hatred is the human expression of feelings, that is directed against a specific object (a person, a group of people, processes, phenomena), characterized by evil, ill-will and that is persistent, with a great intensity and destructivity. 2. Hatred as a crime motive is not included in any Latvian Criminal Law intended to be as a mandatory element for a criminal offense. 3. A controversial question is whether the religious motive is hatred or intolerance motive. In the author's opinion religious motive is human mental functioning internal incentive, passion, disposition, which is based either on a religion preached values or against opinion expressed by the religion. 4. In the author's opinion the fact about instigation of hatred, is basically a crime target materialization, bringing towards a significant level of harmfulness, as it greatly threatens the legally protected interests of public safety and public order, undermining tolerance and integrity. 5. Deep aversion, fear and hatred, could be materialized into defined action, shown as evidence of wrongdoing, which possess a seriousness of a criminal offense.